Leveraging digital infrastructure for sustainable grain production: evidence from China - Han, Jiabin; Ge, Wenting; Chou, Yixiu (Frontiers in Sustainable Food Systems, 2024)
Agriculture faces significant challenges in ensuring global food security while simultaneously reducing resource costs and minimizing environmental impacts. In response, the development of digital infrastructure has emerged as a pivotal solution, offering transformative potential for agricultural systems and aligning with the United Nations Sustainable Development Goals (SDGs). China, with its vast fertile land and large farming population, plays a crucial role in the global food system and contributes substantially to the world's grain supply. This study focuses on China as a case study, analyzing data from 277 prefecture-level cities from 2011 to 2021, and employing a double machine learning model to empirically assess the impact of digital infrastructure on grain production capacity. Results reveal that digital infrastructure significantly enhances grain production. Mechanism analysis results indicate that digital infrastructure construction drives agricultural technological advancements and farmland scale, contributing to increased production capacity. Heterogeneity analysis results show that the impact of digital infrastructure construction is significant in major grain-producing regions and the central-eastern regions, while its effects are relatively limited in grain production-consumption balanced regions, main grain consumption regions, and the western regions. Relevant policy implications are suggested for strengthening digital infrastructure construction in rural areas with local conditions to improve grain production capacity, enhance sustainable food production, and contribute to global food security.